Caracterização do colágeno da pele de tilápia do Nilo (Oreochromis Niloticus) utilizado em curativos oclusivos e avaliação do potencial de regeneração óssea guiada em defeitos de ângulo mandibular de ratos - Lima Verde, Maria Elisa Quezado (2023)
Nile tilapia skin (NTS) is a byproduct from fish-farming activities in tropical and subtropical regions. The skin, scale, and spine of various fish species have been extensively demonstrated as a potential source of native extracellular matrix proteins for use in regenerative medicine. Thus, aiming to review the literature on the use of extracellular matrix proteins derived from Nile tilapia as natural scaffolds for tissue regeneration, the first chapter of this thesis highlights studies that have pointed to tilapia as a satisfactory source of collagen due to its quality and cost-effectiveness, with good in vivo and in vitro responses, especially studies involving the skin as the main source of production. The 2 nd chapter of this thesis described the ultrastructural aspects of NTS, assessed its collagen amount and organization, and compared quantitative methods of histochemical and immunohistochemical analysis (in all sterilization steps for use in burn dressings). In natura skin (IN), chemical sterilization (CH), additional irradiation (30 kGy) (IR), and skins used in burn treatment (BT) were compared. A significant amount of type- I collagen is observed despite sterilization, although clinical application further reduces type I collagen. This quantification showed reliable results through immunohistochemistry and/or Picrosirius Red. Both methods not only exhibit no difference in the quantified value (p = 0.247), but a positive correlation (r = 0.927; 95 % CI = 0.720–0.983) was observed between them, with concordance for collagen quantification in similar samples, presenting a low systematic error rate (Dalberg coefficient: 6.70). Clinical studies have shown that NTS-derived occlusive dressings demonstrated superior clinical outcome than conventional dressings for burn treatment, which encouraged the use of NTS in soft tissue regeneration. However, the use of NTS to treat hard tissue defects has been scarcely studied. Therefore, in the 3 rd chapter of this thesis, we sought to determine the regenerative potential of NTS in mandibular critical-sized defects for guided-bone regeneration (GBR). In a murine model (n=8/group), we performed bilateral critical-size mandibular bone defects in order to test two formulations of NTS: a dermal skin membrane scaffold (DS), and the lyophilized skin (LS). A commercial collagen (BioGide®) was used as a positive control (C+), whereas no membrane was used as a negative control (C-). Animals were euthanized after 1 and 16 weeks for further radiographical and histological analysis. Our results show that, after 16 weeks, there is absence of inflammatory infiltrate in most groups, with exception of DS, which showed persistence of moderate inflammation associated with membrane remnants and presence of multinucleated giant cells. A prominent bone formation was observed in C+ group (p<0.05), whereas the bone formation in DS and LS groups was not statistically different when compared to either C+ or C- group (p>0.05). Despite being a very promising biomaterial and presenting clinical benefits in soft tissue regenerative procedures, the application of the two tested formulations of Nile tilapia skin collagen did not show favorable results for GBR. Further formulations and adjustments to slow the membrane resorption process and decrease local cytotoxicity are necessary for future clinical applications aimed at GBR.